Structural and Improper Ferroelectric Properties of TbInO3 Single Crystal Grown by Laser Floating Zone - Chang Min; You Wu; Yanbin Li; Chunming Zhou; Sang-Wook Cheong; Xiaosong Lu; Tianyuan Zhou; Le Zhang (Crystals, 2023)
The honeycomb TbInO3 has attracted wide research attention due to its fascinating physical properties. However, TbInO3 single crystal was difficult to grow owing to the high melting point and serious volatilization of indium during the crystal growth. In this study, the volatilization of the indium element was effectively suppressed by controlling the growth atmosphere and pressure. The excess ratio of indium oxide was determined, and pure hexagonal TbInO3 crystal was obtained by the laser floating zone method. Systematic studies on the crystal structure and optical and ferroelectric properties were carried out. The structure distortion resulted in the improper geometric ferroelectric revealed by single crystal diffraction and Raman spectrum measurements. The topological vortex domains and P-E hysteresis loop demonstrated the presence of ferroelectricity. TbInO3 crystal has great potential application in vortex memory.